2015
DOI: 10.4236/opj.2015.58025
|View full text |Cite
|
Sign up to set email alerts
|

Classification of African Mosaic Virus Infected Cassava Leaves by the Use of Multi-Spectral Imaging

Abstract: In this work, we have used multispectral imaging technology to classify cassava leaves infected by African mosaic virus by the use of their unique spectral finger print. The spectra are extracted from transmission, reflection and diffusion of their multispectral images; they have been then analyzed with statistical multivariate analysis techniques. Principal component analysis (PCA) has been used followed by K-means and Ascending Hierarchical Classification (AHC) to endorse the classification. The contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This index variation translated by a high diffusion spectrum at 590 nm and 700 nm to 940 nm for the leaves under treatment may be related to the presence of the 2,4-D molecules in the mesophilic tissue creating additional layers at the base of the disorganization of the pigment concentration of the leaves. It may also be related to the geometry of the leaf, the physicochemical and optical properties (transmission, absorption, and reflection) [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This index variation translated by a high diffusion spectrum at 590 nm and 700 nm to 940 nm for the leaves under treatment may be related to the presence of the 2,4-D molecules in the mesophilic tissue creating additional layers at the base of the disorganization of the pigment concentration of the leaves. It may also be related to the geometry of the leaf, the physicochemical and optical properties (transmission, absorption, and reflection) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several methods exist for monitoring the health of plants [5] [11] [12] and are based on the interaction between light and matter. Multi-spectral imaging [13] [14] [15] and fluorescence [16] [17] [18] have also shown their ability to monitor the health of plants and to discriminate against certain diseases. We combine these two techniques to discriminate two types of maize plant (healthy and treated with herbicide plants) to predict the physiological state of a new database and especially to understand the impact of the herbicide on the physiology of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the use of multispectral microscopy in the detection of malaria without fluorescent labelling of cells 10,11 and the early detection of plant diseases. 12,13 However, there is a need to improve spatial resolution and noise performance in these systems. We, therefore, present an implementation of a TMSR-based microscopy system that seeks to improve thin blood smear image contrast via a multispectral approach.…”
Section: Introductionmentioning
confidence: 99%
“…Cassava (Manihot esculentus, Crantz), belonging to Euphorbiaceae family, is a perennial shrub with edible roots which grows in both tropical and subtropical areas of the world [31]. It originated from tropical America (Brazil) and was first introduced into Africa in Congo basin by Portuguese traders around 16 th Century [19].…”
Section: Introductionmentioning
confidence: 99%